PERAN PKK DALAM SWAKELOLA SAMPAH ORGANIK DI KOTA DENPASAR - Puspawati, Dewa Ayu; Ariati, Putu Eka Pasmidi (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
Tegal Harum is a village located in the city of Denpasar where two PKK groups in the village, namely PKK from Banjar Asta Bhuana and Buana Kubu, experienced problems in managing garbage. The density of the population in this area has implications for the abundant amount of waste produced. On the other hand, residents do not understand the waste management at the household level. So far, they only rely on garbage collectors who come to pick and manage the garbage from residents? homes. Some problems that occur as the garbage collectors do not come is having the garbage scattered by stray dogs or cats. Furthermore, ugly litters cause unpleasant odors, and even become homes for mosquitoes or mice which eventually sources of illness for the surrounding residents. PKM PKK Banjar Asta Bhuana and Buana Kubu aims at (1) in terms of environment: overcoming air pollution, eliminating the breeding grounds for disease vectors, and tackling floods and the potential for drainage pollution; (2) management aspects: increasing human resources in waste management at the household level with simple technology and training the management of waste disposal into organic fertilizer to improve soil quality; (3) aspects of the use of solid and liquid fertilizers: socializing the use of solid and liquid organic fertilizers as a result of household composters to replace the role of chemical fertilizers in fertilizing the soil and triggering the interest of PKK members to plant again in their home yard. The Community Partnership Program (PKM) of the PKK group in the self-management of organic waste was carried out through counseling and training methods. Counseling was carried out regarding the importance of environmental sanitation, sorting organic and inorganic waste, and using organic fertilizer. Then, training includes household waste management, simple use of home composter technology, and the procedure for harvesting solid and liquid fertilizers produced by the composter. From the activities that have been carried out, the results obtained are as follows: (1) PKK groups were able to carry out self-management of organic waste independently and sustainably through waste segregation and the use of composter technology, (2) production of solid and liquid organic fertilizers to meet fertilizer needs in households, and (3) improving partner's quality of life, health, and environment.